A Review on Parkinson’s Disease and Cerebellar Ataxia and its Management through Sarvangdhara - Yadav, Abhishek; Kumar, Ajay; Singhal, Tina (International Research Journal of Ayurveda & Yoga, 2024)
Parkinson’s disease (PD) is a type of movement disorder that can affect the ability to perform common, daily activities. The most common motor symptoms of PD are tremors (a form of rhythmic shaking), stiffness or rigidity of the muscles, and slowness of movement (called bradykinesia). A person with PD may also have trouble with posture, balance, coordination, and walking. Common non-motor symptoms of PD include sleep problems, constipation, anxiety, depression, and fatigue, among others. This neurodegeneration disorder has a slow onset but is progressive. Ataxia (from the Greek, meaning “not ordered”) is a term used to describe a number of abnormal movements that may occur during the execution of voluntary movements including incoordination, delay in movements, dysmetria (inaccuracy in achieving a target), dysdiadochokinesia (inability to perform movements of constant force and rhythm), and tremor. The role of the cerebellum is concerned with the timing, coordination, and integration of movements, including eye movements and speech. Therefore, lesions affecting the cerebellum would result in a disorder of movement coordination often termed as cerebellar ataxia. Ayurveda includes many different treatment regimes and one of them is Sarvangdhara. Sarvangdhara is a form of Ayurvedic massage remedy that involves pouring warm treated oil over the whole body. The word “Sarvangdhara” is deduced from two Sanskrit words – sarvang means whole body and dhara means flow.